Lyric Folk Poetry of the Serbs from Kosovo and Metohija: An Overview - Pitulić, Valentina D. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
This paper provides a general overview of the lyric folk poems of the Serbs from Kosovo and Metohija, an integral part of the broader lyric folk tradition that constitutes the poetic heritage of the Serbian people. Shaped by the specific socio-historical circumstances in which it developed, this poetry is characterized by a remarkable richness of motifs alongside a pronounced archaic quality, both of which point to its ancient origins. Despite numerous historical influences, this extensive corpus of lyric poetry has preserved its distinctiveness through the continued use of established stylistic formulas—formulas that most faithfully reflect the spiritual and communal life of the community in which it originated.An analysis of these poems reveals that one of their most distinctive features is their layered composition, manifested in the complex interweaving of pagan and Christian symbolic elements. The diversity of motifs invites deeper exploration of the meanings embedded in the archetypal layers of collective consciousness, particularly as expressed in ritual, religious, amatory, and domestic verse. Recurring motifs—the cosmic wedding, the city built upon a cloud, the symbolic significance of plants, the cult of the earth, and various aspects of ritual and customary practice—suggest that a comprehensive interpretation of the lyric tradition of this region requires an interdisciplinary approach that extends beyond the scope of the present study.The overview presented here serves both as a synthesis of existing scholarship and as a point of departure for future research, particularly concerning the interaction between pagan and Christian symbolic systems and the recurring motifs of the sun, the city built upon a cloud, fire, water, and earth. The study affirms that the distinctive lyric voice of the Serbs from Kosovo and Metohija constitutes a poetic achievement of exceptional cultural significance and continues to offer a productive field for further scholarly investigation.
Keywords: Kosovo and Metohija; folklore; lyric poetry; paganism; Christianity; the sun; ritual; symbolism; archetype